Effects of Three Distinct 2-Week Long Diet Strategies After Transport on Weaned Pigs' Short and Long-Term Welfare Markers, Behaviors, and Microbiota - Parois, Severine P.; Duttlinger, Alan W.; Richert, Brian T.; Lindemann, Stephen R.; Johnson, Jay S.; Marchant-Forde, Jeremy N. (Frontiers in Veterinary Science, 2020)
Alternative feed supplements have shown promising effects in performance, but effects on welfare have had little evaluation. In the present study, we aimed at evaluating the effect of diet supplementation on welfare indicators. A total of 246 piglets were weaned and transported for a 12h. After transport, they were assigned to one of 3 diets fed for a 14-day period: A – an antibiotic diet including chlortetracycline and tiamulin, NA – a control diet without any antibiotic or feed supplement, GLN – a diet including 0.20% L-glutamine. After the 14-day period, all piglets were fed the same diet. Tear staining was measured 11 times post-weaning (from d0 to 147). Skin lesions were counted before and after weaning (d-2, 2 and 36). Novel object tests (NOT) were done in groups 4 times post-weaning (d17, 47, 85, 111). Samples for 16S microbial DNA composition were collected prior to transport (d0), following the 14-day period (d14) and at the conclusion of the nursery phase (d34). The NA pigs appeared less interested by novel objects. On d17, they avoided the object less than A pigs (P < 0.05). They spent less time exploring the object on d85 and took longer to interact with the object on d111 than A and GLN pigs (P < 0.05). NA pigs also appeared more sensitive to environment and management. They had larger tear stains than GLN pigs on d84 and 110 (P < 0.05). On d2, NA pigs had more lesions than A and GLN (P < 0.01). In terms of microbiota composition, GLN had higher -diversity than A and NA (P < 0.001). Differences between dietary treatments were absent at d0, were all demonstrated at d14 and disappeared at d34. Pearson correlations between aggression, stress and anxiety indicators and bacterial populations were medium to high from 0.31 to 0.69. The results demonstrate that short-term feeding strategy can have both short- and long-term effects on behavior and welfare, that may partly be explained by changes in gut microbiota composition. Supplementation with GLN appears to confer similar benefits to, and thus could be a viable alternative to dietary antibiotics.